(untitled) - Beckmann, Poul (Oxford, 2004)
This practical guide to the assessment and repair of historic buildings is invaluable for structural engineers, architects, surveyors and builders working in all aspects of building conservation. Taking a practical step-by-step approach, the authors discuss the appraisal of buildings and the differences in structural behaviour between new and existing structures. Each stage in the appraisal is explained, using examples from the authors' own work. each major construction material is assessed in detail, with separate sections on masonry, concrete, timber and the particularly complex issues of iron and steel framed buildings. Techniques for testing the ability of a building to continue its existing use or to be converted to a new use are explained.
Keywords: Historic buildings,Historic buildings,Historic buildings,Structural analysis (Engineering),Thiết kế kiến trúc,Thiết kế xây dựng,Phân tích cấu trúc; Conservation and restoration,Maintenance and repair,Remodeling for other use